Optimizing English Learning with Mind Mapping: A Classroom Application at SMPN 7 Muaro Jambi - Adang Ridwan; Ria Karmila; Mahdayeni; Chichi Apriani (International journal of technology and education research, 2025)
This study investigates the application of the mind mapping technique as a teaching strategy to optimize students’ English vocabulary learning. This qualitative research involved one English teacher as the subject, and the data were collected through observations, interviews, and documentation. The data were then analyzed using descriptive analysis. The findings reveal that the teacher’s strategy in implementing mind mapping plays a significant role in improving students’ vocabulary mastery. However, several challenges emerged, such as limited explanation, time constraints, and the lack of additional materials, which caused difficulties in spelling and memorization. To overcome these problems, the teacher combined multiple strategies, including presenting vocabulary items with diagrams, using visual aids, and emphasizing clear word structures. Furthermore, the teacher applied essential mind mapping principles, such as using colors, images, keywords, associations, and central images to present ideas more effectively. These strategies ultimately made vocabulary learning more engaging, creative, and effective, enabling students to memorize words more easily, quickly, and enjoyably.